Analisis Gangguan Penyulang Dengan Menggunakan Diagram Pareto dan Diagram Fishbone di UP3 di Bojonegoro - Nissa, Dini Y.C,; ., Iriani (Jurnal Sains dan Teknologi (JSIT), 2024)
Feeder interference is an important problem in the electricity system because it can cause unplanned blackouts. With society's increasing need for electricity, it is very important to understand the components that cause feeder interference. Feeder problems can be caused externally or internally. This research was used to determine the level of causes of feeder disturbances at UP3 Bojonegoro and also the root causes of these disturbances. To realize the objectives of this research, this research uses Pareto and fishbone diagrams. The highest level of problems lies in internal factors, namely insulators, conductors and arresters. Meanwhile, external factors are the result of animals and residents' activities. Then, for employment factors that influence feeder disruption, such as lack of practice regarding maintenance or restoration. Therefore, this research contributes to efforts to maintain the sustainability of the electricity system, with the hope of providing a better view of this problem and motivating the implementation of more effective preventive measures.